To Be, or Not to Be: Paraphrased - Rosenbridge, Bardsley (punctum books, 2016)
To Be, or Not to Be: Paraphrased is an expanding deconstruction of Hamlet's famous existential question, achieved by putting the line through paraphrasing software 50 times. With each permutation, the quotation grows longer and its meaning is distorted, causing the question to question its own existence by acting as a faulty self-replicator, a nonsensical self-affirmation that destroys itself in the process of becoming. This controlled explosion of a sentence was performed by Bardsley Rosenbridge as part of his work with the Dark Meaning Research Institute, a group of parasemantic experimenters developing innovative ways to extract hidden meaning from the world around us.